Oscillation criteria in neutral equations of n order with variable coefficients - D. A. Georgiou; C. Qian (International Journal of Mathematics and Mathematical Sciences)
Consider the n-order neutral delay differential equation dndtn[y(t)+P(t)y(t−τ)]+Q(t)y(t−σ)=0 where P,Q∈C[[t0,∞),ℝ] and the delays τ and σ are nonnegative real numbers. In this paper we examined the oscillatory behavior of the solutions of the above equation using techniques which allow the relaxation of the restrictions which has been introduced previously. We illustrate new type of conditions which improve and extend known results, by relaxing hypotheses that P is constant and Q is τ-periodic.